Characteristics and conditions of entrepreneurship in Eastern Europe - Marin A. Marinov; Svetla Trifonova Marinova (Journal for East European Management Studies, 1996)
Establishing of new small businesses is an intensive process in the whole of Eastern Europe. As they are new, most of them are in the introductory phases of their existence (survival, consolidation and control). Contemporary industrial and market structure in the countries of Eastern Europe provides entrepreneurs with many opportunities for niche company creation. However, many problems exist related to the lack of resources (mostly financial), inadequate knowledge and skills in management and marketing needed in market economies, insufficient availability of business support organisations combined with inappropriate understanding and attitude among managers in the newly created businesses towards the existing business support organisations. – – Der Aufbau von neuen Kleinunternehmen stellt in ganz Osteuropa einen intensiven Prozeß dar. Die meisten von ihnen stehen noch ganz am Anfang, in den ersten Phasen ihrer Existenz (Überleben, Konsolidierung und Kontrolle). Die gegenwärtigen Industrie- und Marktstrukturen in den osteuropäischen Ländern verschaffen Unternehmern viele Möglichkeiten zur Gründung von Nischenunternehmen. Dennoch bestehen eine Vielzahl von Problemen im Zusammenhang mit fehlenden Ressourcen (meist finanzieller Art), unangepaßtes Wissen und oft fehlende Fähigkeiten im Management und Marketing, oft fehlende Unterstützungsorganisationen verbunden mit ungenügenden Verständnis und Einstellung der Führungskräfte in den neu gegründeten Unternehmen existierenden Unterstützungsorganisationen gegenüber.
Keywords: 650